The Zobel Nexus - Flores, Patrick D. (Archīum Ateneo, 2024)
Fernando Zobel is an important figure in Philippine art history. His influence is wide and deep, from art making to formation of taste and to the production of discourse on iconography and identity. This essay focuses on his role in generating critical texts on the history of art in the Philippines, initiating a much-needed discussion on the categories of form, the cultural context of style, and the criteria for evaluating the value of objects. As a collector and connoisseur, Zobel endeavored to significantly set the terms with which the history of colonial and modern art would be written. Such an effort deserves to be revisited and subjected to critique, with the view of tracing the genealogy of the discourse of art history and prospecting new perspectives on the historiography of the colonial and the modern. Zobel is an exemplary personage in this regard because he was a polytropic agent. He made art, collected it, and historicized it. It finally offers analysis, too, of the political economy underlying this discourse; Zobel belonged to an economically ascendant clan in the country, created a coterie of taste makers, and pursued an “internationalist” ideal in the quest for modernism. Across the different roles that Zobel played may be discerned important aspects of consciousness, or better still, ciphers of the identity-effect: the “colonial,” the “Filipino,” the “modern,” and “class.”